Genetic and morphological variation in sexual and asexual parasitoids of the genus Lysiphlebus - an apparent link between wing shape and reproductive mode - Petrović, Andjeljko; Mitrović, Milana; Ivanović, Ana; Žikić, Vladimir; Kavallieratos, Nickolas G; Starý, Petr; Bogdanović, Ana Mitrovski; Tomanović, Željko; Vorburger, Christoph (BMC evolutionary biology, 2015)
BACKGROUND: Morphological divergence often increases with phylogenetic distance, thus making morphology taxonomically informative. However, transitions to asexual reproduction may complicate this relationship because asexual lineages capture and freeze parts of the phenotypic variation of the sexual populations from which they derive. Parasitoid wasps belonging to the genus Lysiphlebus Foerster (Hymenoptera: Braconidae: Aphidiinae) are composed of over 20 species that exploit over a hundred species of aphid hosts, including many important agricultural pests. Within Lysiphlebus, two genetically and morphologically well-defined species groups are recognised: the "fabarum" and the "testaceipes" groups. Yet within each group, sexual as well as asexual lineages occur, and in L. fabarum different morphs of unknown origin and status have been recognised. In this study, we selected a broad sample of specimens from the genus Lysiphlebus to explore the relationship between genetic divergence, reproductive mode and morphological variation in wing size and shape (quantified by geometric morphometrics). RESULTS: The analyses of mitochondrial and nuclear gene sequences revealed a clear separation between the "testaceipes" and "fabarum" groups of Lysiphlebus, as well as three well-defined phylogenetic lineages within the "fabarum" species group and two lineages within the "testaceipes" group. Divergence in wing shape was concordant with the deep split between the "testaceipes" and "fabarum" species groups, but within groups no clear association between genetic divergence and wing shape variation was observed. On the other hand, we found significant and consistent differences in the shape of the wing between sexual and asexual lineages, even when they were closely related. CONCLUSIONS: Mapping wing shape data onto an independently derived molecular phylogeny of Lysiphlebus revealed an association between genetic and morphological divergence only for the deepest phylogenetic split. In more recently diverged taxa, much of the variation in wing shape was explained by differences between sexual and asexual lineages, suggesting a mechanistic link between wing shape and reproductive mode in these parasitoid wasps.
Keywords: Wasps; křídla zvířecí; fylogeneze; sršňovití; Reproduction, Asexual; nepohlavní rozmnožování; Animals; Reproduction; rozmnožování; Aphids; Phylogeny; zvířata; mšice; Wings, Animal